Risk of esophageal thermal injury during catheter ablation for atrial fibrillation guided by different ablation index. Issue 7 (29th May 2020) - Zhang, Zu‐Wen; Zhang, Pei; Jiang, Ru‐Hong; Liu, Qiang; Sun, Ya‐Xun; Yu, Lu; Lin, Jian‐Wei; Chen, Shi‐Quan; Sheng, Xia; Fu, Guo‐Sheng; Jiang, Chen‐Yang
Abstract: Background: During ablation for atrial fibrillation (AF), energy delivery toward the left atrial posterior wall may cause esophageal injury (EI). Ablation index (AI) was introduced to estimate ablation lesion size, however, the impact of AI technology on the risk of EI has not been explored. Method: From March 2019 to December 2019, 60 patients with paroxysmal AF undergoing first‐time ablation were prospectively enrolled. The first 30 consecutive patients were ablated with the AI target value of 400 (AI‐400 group), and the later 30 consecutive patients were ablated with the AI target value of 350 at the posterior wall (AI‐350 group). Endoscopic ultrasonography was used to evaluate EI postablation. EI was classified as a category 1 (erythema or erosion) or a category 2 (hematoma or ulceration). Results: Compared with the AI‐400 group (59.9 ± 8.4 years; male, 60%), the AI‐350 group (59.1 ± 9.9 years; male, 50%) had a lower incidence of EI (3.3% vs 26.7%, P  = .03). There was no significant difference in the percentage of first‐pass PVI between the AI‐400 group and the AI‐350 group (left PVI: 80% vs 73.4%, P  = .54; right PVI: 80% vs 60%, P  = .1). Neither ablation time nor fluoroscopy time was significantly different between the AI‐400 group and the AI‐350 group. Conclusions: AF ablation guide by AI target value of 350 may reduce esophageal thermal injury and has a similar efficiency on the acute success rate of first‐pass PVI compared with an AI target value of 400 at the posterior wall.